Analisis Pendekatan CBSA dan Pembelajaran Berdeferensiasi dalam Pembelajaran Bahasa Indonesia - Ni Nyoman Kurnia Wati; Nyoman Ayu Putri Lestari; I Nyoman Sudiana; Ida Bagus Putrayasa (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to analyze the CBSA approach and differentiation learning in Indonesian language learning. This research was conducted by analyzing the literature on studies that took the CBSA approach and differentiation learning in Indonesian language learning. The data obtained in this study are secondary data. Secondary data is a variety of information that has been there before and deliberately collected by researchers that is used to complement the needs of research data. This study uses qualitative descriptive data analysis. Based on the literature analysis on the CBSA approach and differentiated learning, it can be concluded that: 1) the CBSA approach, especially in Indonesian subjects, can improve learning outcomes, reading skills, and literacy skills of elementary school students. This indicates that the CBSA approach has been widely studied and deserves to be developed in other studies according to their respective variables, 2) differentiated learning in Indonesian language learning makes a positive contribution to learning outcomes, students' literacy skills and even becomes a reflection material for teachers in schools. basic, 3) there are some similarities in the CBSA approach and differentiated learning in the independent learning curriculum so that the connection is that the CBSA approach can be integrated in differentiated learning, especially in Indonesian subjects